Medicaid Work-Reporting Requirements Under HR 1 and Insufficient or Inconsistent Work Hours - Paul R. Shafer; Timothy H. Callaghan; David M. Anderson (JAMA Health Forum, 2026)
Importance House Resolution 1 (HR 1) of the 119th US Congress (2025-2026), known as the One Big Beautiful Bill Act, created national work-reporting requirements for adult Medicaid expansion enrollees starting by January 1, 2027. Although many expect the administrative burdens associated with work-reporting requirements to be the primary source of disenrollment, the impact of variable work hours and/or part-time work on potential disenrollment from Medicaid among low-income working adults is unknown. Objective To assess the risk of noncompliance with national Medicaid work-reporting requirements due to insufficient and/or variable work hours after enactment of HR 1. Design, Setting, and Participants This cross-sectional study used data from the 2023 to 2025 Current Population Survey (US) to describe employment of adults between 18 and 64 years of age who were plausible Medicaid-expansion enrollees. The prevalence of being at risk of noncompliance was estimated, and modified Poisson regression models were used to assess differential risk based on demographic characteristics. Data were analyzed from February through June 2026. Exposure Work-reporting requirements under HR 1. Main Outcomes and Measures Risk of noncompliance due to usually being near the 20-hours-per-week threshold and/or for reporting variable hours. Results The analytic sample comprised 19 476 observations, representing a mean annual weighted population of more than 16 million individuals (mean age, 41.1 [95% CI, 40.8-41.3] years; 49.8% female and 50.2% male individuals), most of whom were unmarried (71.8%) and non-Hispanic White (47.9%) with a high school level or equivalent education (41.0%). Among them, we estimated that 19.8% of those potentially subject to work reporting requirements and working are at risk of noncompliance, by usually being near the hours threshold (13.6%) and/or reporting variable hours (7.6%). Female individuals had a 22% higher probability (adjusted risk ratio [aRR], 1.22; 95% CI, 1.11-1.35) of being at risk of noncompliance, whereas married respondents had an 18% lower probability (aRR, 0.82; 95% CI, 0.74-0.92). Significant variation was also observed by race and ethnicity and by education level. Conclusions and Relevance This cross-sectional study found near full-time mean hours per week among working adults age 18 to 64 years enrolled in or likely eligible for Medicaid expansion. However, nearly one-fifth were at risk of noncompliance due to insufficient or variable hours.